2011
DOI: 10.1249/mss.0b013e3181e93210
|View full text |Cite
|
Sign up to set email alerts
|

Novel Precooling Strategy Enhances Time Trial Cycling in the Heat

Abstract: This new precooling strategy represents a practical and effective technique that could be used by athletes in preparation for endurance events undertaken in hot and humid conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
123
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(140 citation statements)
references
References 31 publications
12
123
5
Order By: Relevance
“…Ice-slurry ingestion and cold water immersion precooling resulted in improved running times to exhaustion in the heat compared to control, but these separate precooling treatments were not different from each other, indicating that both techniques are comparable (Siegel et al, 2012). Furthermore, in another study that included water immersion and ice-slurry ingestion prior to a cycling time trial in the heat, both treatments resulted in improved performance compared to control, but ice-slurry had a larger effect on power output during one stage of the race and resulted in better overall performance (3.0%) than cold water immersion (1.1%) (Ross et al, 2011). Furthermore, other studies have shown an improvement in running time to exhaustion by ~10 min and cycling time trial performance by 6.5% accompanied with lower T c after ice-slurry ingestion compared with cold or tap water ingestion (Siegel et al, 2010;Ihsan et al, 2010).…”
Section: Combined Precooling and Warm-upmentioning
confidence: 94%
See 4 more Smart Citations
“…Ice-slurry ingestion and cold water immersion precooling resulted in improved running times to exhaustion in the heat compared to control, but these separate precooling treatments were not different from each other, indicating that both techniques are comparable (Siegel et al, 2012). Furthermore, in another study that included water immersion and ice-slurry ingestion prior to a cycling time trial in the heat, both treatments resulted in improved performance compared to control, but ice-slurry had a larger effect on power output during one stage of the race and resulted in better overall performance (3.0%) than cold water immersion (1.1%) (Ross et al, 2011). Furthermore, other studies have shown an improvement in running time to exhaustion by ~10 min and cycling time trial performance by 6.5% accompanied with lower T c after ice-slurry ingestion compared with cold or tap water ingestion (Siegel et al, 2010;Ihsan et al, 2010).…”
Section: Combined Precooling and Warm-upmentioning
confidence: 94%
“…Two studies included a standard 20-min warm-up session after three different methods of body cooling and prior to completion of a cycling time trial (Quod et al, 2008;Ross et al, 2011). However, the designs utilized do not permit one to identify the separate and combined effects of precooling and warm-up on subsequent exercise performance.…”
Section: Combined Precooling and Warm-upmentioning
confidence: 99%
See 3 more Smart Citations